2015
DOI: 10.3390/biom5042435
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Ion Pairs of Biological Macromolecules

Abstract: Ion pairs (also known as salt bridges) of electrostatically interacting cationic and anionic moieties are important for proteins and nucleic acids to perform their function. Although numerous three-dimensional structures show ion pairs at functionally important sites of biological macromolecules and their complexes, the physicochemical properties of the ion pairs are not well understood. Crystal structures typically show a single state for each ion pair. However, recent studies have revealed the dynamic nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 172 publications
(268 reference statements)
2
29
0
2
Order By: Relevance
“…Interactions with the DNA backbones and the DNA bases, involving salt bridges or hydrogen bonds, have lifetimes that are typically of the order of tens to hundreds of picoseconds. This is in line with recent NMR and simulations studies of the dynamics of lysine salt bridges in protein/DNA complexes (5,41,42). A very recent extension of this work shows that, in contrast, arginines bound to guanine in a bidentate manner within a Zn-finger complex are much less dynamic (43).…”
Section: Discussionsupporting
confidence: 90%
“…Interactions with the DNA backbones and the DNA bases, involving salt bridges or hydrogen bonds, have lifetimes that are typically of the order of tens to hundreds of picoseconds. This is in line with recent NMR and simulations studies of the dynamics of lysine salt bridges in protein/DNA complexes (5,41,42). A very recent extension of this work shows that, in contrast, arginines bound to guanine in a bidentate manner within a Zn-finger complex are much less dynamic (43).…”
Section: Discussionsupporting
confidence: 90%
“…Oxygen-to-sulfur substitutions might also perturb the dynamic equilibrium of the contact ion-pair (CIP) and solvent-separated ion-pair (SIP) states. [21] As we recently demonstrated, the intermolecular ion pairs of Lys side-chain and DNA phosphate groups undergoes dynamic transitions between the CIP and SIP states on a sub-nanosecond timescale. [12] Oxygen-to-sulfur substitution in DNA phosphate might shift the CIP-SIP equilibrium of the intermolecular ion pair toward the SIP state, mobilizing the Lys NH 3 + group.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our previous NMR and molecular dynamics studies showed that the Lys 15 NH 3 + groups that exhibit sizable h3 J NP coupling with the DNA 31 P nuclei undergo dynamic transitions on a sub-nanosecond timescale between the contact ion-pair and solvent-separated ion-pair states. 7,9,31 …”
mentioning
confidence: 99%